Kebijakan Standar Pendidik dan Tenaga Kependidikan di MTS Laboratorium UINSU - Indah Sukmawan; Nazla Khairunnisa Damanik; Zakiyah Darajah; Irwansyah Siagian; Tengku Darmansah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to analyze policies regarding the standards of educators and education personnel at MTs Laboratorium UINSU, focusing on the implementation, challenges, and perceptions of school stakeholders. Using qualitative methods, the study involved interviews with school leaders, teachers, and staff to understand how these standards are applied and their impacts on educational quality. Findings indicate that while MTs Laboratorium UINSU has established policies aligned with national education standards (Standar Nasional Pendidikan), there are challenges related to understanding policy details, implementation consistency, and professional development opportunities.